IMPROVING BEGINNING READING ABILITY WITH LETTERS CARDS IN CLASS 1 STUDENTS OF STATE ELEMENTARY SCHOOL 005 KEPENUHAN - Herawati Herawati (Indonesian Journal of Basic Education, 2021)
This study aims to improve the ability to read beginning with letter card media in grade 1 State Elementary School 005 Kepenuhan. This type of research is classroom action research (CAR) which is descriptive qualitative using a qualitative approach that is strengthened by a quantitative approach, taking the background of the 005 Kepenuhan State Elementary School. The subjects of this study were grade 1 students at State Elementary School 005 Kepenuhan, while the object of this research was the improvement of initial reading skills using letter cards on the theme of Living and Non-Living Objects Around Me. This research was conducted in three cycles and through four stages which include: (1) planning, (2) implementation, (3) observation, (4) reflection. Data were obtained through observation, interviews, reading tests, and documentation. The results showed that letter card media could improve students' initial reading skills. The increase in student learning activities can be measured from evaluations I, II, and III with the value of student learning activities in the first cycle of 68.04%, the second cycle of 73.04%, and the third cycle of 75.86%.